Self-Efficacy of North Maluku Athlete Students at the National Student Sports Week (POMNAS) DKI Jakarta - Syahril Adam; Eva Faridah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study is to reveal the self-efficacy of North Maluku athlete students at the National Student Sports Week (POMNAS) 2019 in DKI Jakarta. So far, there have been many quantitative research publications on self-efficacy, but the results obtained have not explored the psychological dynamics of athletes more deeply. Through this study, researchers found new more in-depth facts related to athletes' self-efficacy. This study uses a qualitative approach. Data collection is done when the athletes have finished competing, with the hope that the data obtained is more accurate because they are still in competition atmosphere. The subjects in this study were North Maluku athlete students who participated in the 2019 POMNAS activities in DKI Jakarta. The results of this study indicate that North Maluku Athlete students have high self-efficacy, this is indicated by the athletes knowing the level of each series of training programs undertaken, being able to complete a series of given training programs, and having the ability to complete the entire series of training programs.